HUMAN-CENTERED AI IN TRANSLATION: PARTNERSHIP OR PRETENSE - Ugiloy Karimova (Bright Mind Publishing, 2025)
The rapid integration of Artificial Intelligence (AI) into the field of translation has radically altered the process of text creation, mediation, and dissemination across linguistic and cultural borders. Defenders of "human-centered AI" argue that these innovations can increase efficiency and expand accessibility, and in turn create a harmonious rapport between human translators and cognitive systems. However, critics warn that such collaborations are often shallow, befogging salient questions of labor displacement, cultural homogeneity, and ideological hegemony. This paper responds to the timely question: is human-centered AI in translation truly a partnership, or an illusion disguising structural inequalities?
Keywords: Human-focused artificial intelligence in translation, automated translation, computer-aided translation tools, collaboration, translation agency, post-editing procedures, ethical implications.